Dexamethasone for treating SARS-CoV-2 infection: a systematic review and meta-analysis - Ferreto, Lirane Elize Defante; Bortoloti, Durcelina Schiavoni; Fortes, Paulo Cezar Nunes; Follador, Franciele; Arruda, Gisele; Ximenez, João Paulo; Wendt, Guilherme Welter (São Paulo Medical Journal, 2021)
BACKGROUND: Considering the disruptions imposed by lockdowns and social distancing recommendations, coupled with overwhelmed healthcare systems, researchers worldwide have been exploring drug repositioning strategies for treating severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). OBJECTIVE: To compile results from randomized clinical trials on the effect of dexamethasone, compared with standard treatment for management of SARS-CoV-2. DESIGN AND SETTING: We conducted a systematic review and meta-analysis in accordance with the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) guidelines in a Brazilian public university. METHODS: We sought to compile data from 6724 hospitalized patients with confirmed or suspected SARS-CoV-2 infection. RESULTS: Treatment with dexamethasone significantly reduced mortality within 28 days (risk ratio, RR: 0.89; 95% confidence interval, CI: 0.82-0.97). Dexamethasone use was linked with being discharged alive within 28 days (odds ratio, OR: 1.20; 95% CI: 1.07-1.33). CONCLUSIONS: This study suggests that dexamethasone may significantly improve the outcome among hospitalized patients with SARS-CoV-2 infection and associated severe respiratory complications. Further studies need to consider both dose-dependent administration and outcomes in early and later stages of the disease. PROSPERO PLATFORM: CRD42021229825.